SISTEM INFORMASI MANAJEMEN ADMINISTRASI BERBASIS WEB MENGGUNAKAN METODE WATERFALL DI INSTITUT TEKNOLOGI DAN BISNIS BINA ADINATA - Sri Hardianti Ningsi; Dedy Hendryadi; Juniarti Iryani (Journal System Information And Computer, 2023)
This research aims to develop a web-based information system that can make it easier for the General Administration Section (BAU) at the Bina Adinata Institute of Technology to manage and archive letters in a computerized manner. This research uses various data collection techniques such as observation, interviews, literature study, and documentation. The software development method used is the waterfall method with the SDLC process, which includes requirements analysis, system design, art, verification and maintenance. System testing is carried out using the black box testing method. Applications and software are built using PHP and MySQL databases. The research results show that a web-based administrative management information system has been successfully built, enabling efficient and accurate storage, search and management of mail data at the Bina Adinata Institute of Technology and Business.